Isokinetic assessment of muscle function according to physical activity level and cardiovascular risk in asymptomatic adults aged 20 to 80 years - V.Z. Dourado; M.B. Nascimento; R.C. Navarro; R.P. da Silva; B.B. Gonze; K.M. Guedes; V.T. Lauria; W.O. Vieira; T.L.V.D.P. Ostolin (Brazilian Journal of Medical and Biological Research)
As limb muscle function is age- and sex-related, both elbow and knee isokinetic muscle functions and their main predictors, such as physical activity level and cardiovascular risk factors, should be determined. We aimed to describe the percentiles of normality of the isokinetic muscle function of the knee and elbow joints. Secondarily, we developed equations to predict muscle function in apparently healthy adults aged 20-80 years, including cardiovascular risk factors. We conducted a cross-sectional study with 1,334 adults. We collected sociodemographic data, self-reported cardiovascular risk, anthropometry, body composition (bioelectrical impedance), moderate-to-vigorous physical activity (MVPA) (triaxial accelerometry), and isokinetic muscle function. Multiple regression analysis was used to develop equations to predict isokinetic muscle function. Percentiles of normality for muscle function were described by sex and age (20-39, 40-59, and >60 years). The models accounted for 49.6-70.9% of the total variability of muscle function, but MVPA and cardiovascular risk slightly influenced the coefficient of determination (additional ΔR2=0.003-0.006). Demographic and anthropometric variables were more relevant predictors of isokinetic muscle function (R2=0.50-0.70) than MVPA and cardiovascular risk. Even though they correlated with muscle function, cardiovascular risk and MVPA failed to explain the variability of muscle function largely determined by anthropometric and sociodemographic data. The percentile values and equations developed will help in interpreting the isokinetic muscle function and improve its clinical use.